2021
DOI: 10.1371/journal.pbio.3001198
|View full text |Cite
|
Sign up to set email alerts
|

Phe-Gly motifs drive fibrillization of TDP-43’s prion-like domain condensates

Abstract: Transactive response DNA-binding Protein of 43 kDa (TDP-43) assembles various aggregate forms, including biomolecular condensates or functional and pathological amyloids, with roles in disparate scenarios (e.g., muscle regeneration versus neurodegeneration). The link between condensates and fibrils remains unclear, just as the factors controlling conformational transitions within these aggregate species: Salt- or RNA-induced droplets may evolve into fibrils or remain in the droplet form, suggesting distinct en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
(154 reference statements)
4
19
0
Order By: Relevance
“…Likewise, substituting threonine for tyrosine confers a polar side chain but eliminates the aromatic ring. Since GFG and FG motifs participate in TDP-43 LLPS and are critical for the formation of TDP-43 fibrils ( Pantoja-Uceda et al, 2021 ), we similarly replaced phenylalanine in GFG or FG/FS motifs with tyrosine or leucine (F276Y/L, F283Y/L, F289Y/L, F313L/Y, F313-316Y/L, F367Y/L, F397Y/L, and F401Y/L) ( Supplementary Figure S1 ). We hypothesized substitutions that abolish the aromatic ring would show more severe effects on TDP-43 RNP condensate formation and transport compared to mutations that preserve the aromatic structure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, substituting threonine for tyrosine confers a polar side chain but eliminates the aromatic ring. Since GFG and FG motifs participate in TDP-43 LLPS and are critical for the formation of TDP-43 fibrils ( Pantoja-Uceda et al, 2021 ), we similarly replaced phenylalanine in GFG or FG/FS motifs with tyrosine or leucine (F276Y/L, F283Y/L, F289Y/L, F313L/Y, F313-316Y/L, F367Y/L, F397Y/L, and F401Y/L) ( Supplementary Figure S1 ). We hypothesized substitutions that abolish the aromatic ring would show more severe effects on TDP-43 RNP condensate formation and transport compared to mutations that preserve the aromatic structure.…”
Section: Resultsmentioning
confidence: 99%
“…We were interested to define the role of these phenylalanine residues in TDP-43 RNP granule transport. Prior studies have demonstrated that mutating or deleting GFG and FG LLPS motifs does not affect phase separation of purified TDP-43 but instead impacts TDP-43 fibrillization ( Li et al, 2018b ; Pantoja-Uceda et al, 2021 ). In addition, F to Y substitutions do not alter TDP-43 dynamics as measured by half bleach fluorescence recovery ( Schmidt et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the structural level, TDP-43 possesses a highly structured N-terminus domain (NTD) [ 66 , 67 ] that controls protein dimerization/oligomerization [ 66 , 68 ]. This NTD is followed by two RNA Recognition Motifs (RRMs) that are responsible for sequence-specific binding to RNA [ 69 , 70 ] and then by an unstructured C-terminus region that plays a fundamental role in phase separation and aggregation [ 71 , 72 , 73 , 74 ].…”
Section: Loss-of-function (Lof) and Gain-of-function (Gof) Mechanisms In Tdp-43 Proteinopathiesmentioning
confidence: 99%